2014
DOI: 10.1177/0907568214543199
|View full text |Cite
|
Sign up to set email alerts
|

Home abroad: Eastern European children’s family and peer relationships after migration

Abstract: IntroductionContemporary patterns of global mobility have led to an increase in the number of families who live separated by borders. Migration is 'a special case of the development of social networks' (Eve, 2010), and its effects on families have only recently become subject of in-depth investigation. The importance of children's relationships for their development, well-being and life opportunities has been emphasised by research. In this article, we are interested in how children's relationships are affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 31 publications
(69 reference statements)
2
27
0
3
Order By: Relevance
“…For instance, Freier and Kahn's (2009) collection of papers addressed how technological environments can be designed to foster rather than harm children's development. More recently, writers have shown that children can maintain relationships with friends and family members located in different cities or overseas (Longhurst 2013;Sime and Fox 2014), explore virtual landscapes with children from different backgrounds around the world (Ash and Gallacher 2011;Dezuanni, O'Mara, and Beavis 2015;Marsh 2010), or positively change learning and communication experiences for children with disabilities or absent and present caregivers (Ganong et al 2012;Holloway and Valentine 2003;Kagohara et al 2013). Freeman and colleagues in their paper (this collection) draw on notions of digital literacy to gain insights into children's use of nature in their neighbourhood via a child-operated Geographical Information System (GIS).…”
Section: Making Sense Of Children's Digital Worldsmentioning
confidence: 99%
“…For instance, Freier and Kahn's (2009) collection of papers addressed how technological environments can be designed to foster rather than harm children's development. More recently, writers have shown that children can maintain relationships with friends and family members located in different cities or overseas (Longhurst 2013;Sime and Fox 2014), explore virtual landscapes with children from different backgrounds around the world (Ash and Gallacher 2011;Dezuanni, O'Mara, and Beavis 2015;Marsh 2010), or positively change learning and communication experiences for children with disabilities or absent and present caregivers (Ganong et al 2012;Holloway and Valentine 2003;Kagohara et al 2013). Freeman and colleagues in their paper (this collection) draw on notions of digital literacy to gain insights into children's use of nature in their neighbourhood via a child-operated Geographical Information System (GIS).…”
Section: Making Sense Of Children's Digital Worldsmentioning
confidence: 99%
“…Migration does not mean, however, the disintegration of family ties, and findings from this study showed the great lengths that migrants go to in order to keep in touch with family members left behind and maintain cultural practices (see also Sime & Fox, 2014b). Children talked very fondly of their relationships with their grandparents and about their regret of having to live separated.…”
Section: Discussionmentioning
confidence: 78%
“…Some of the children interviewed stated that their parents' values were key to their choice of friends, and how there were sometimes tensions between wanting to 'fit in' and adopt practices which would make them popular at school and respecting their families' values (see also Sime & Fox, 2014b).…”
Section: Divergent Practices and Values In Learning About The New Culmentioning
confidence: 97%
“…In a letter to the European Council in May 2014 (see [17]) 38 leading organizations, including UNICEF and Save the Children, urged Member States to address the issue of migrant children's rights, because of their underachievement and marginalisation. Evidence from our research and that of others indicates that children of migrants are marginalised in terms of educational opportunities [18][19][20][21], access to services [22,23] and civic participation [24]. In Scotland, the Government has recently proposed to invest an additional £100 million in education to tackle the attainment gap of all groups [25]-data on the educational attainment of recently arrived migrant children not disaggregated.…”
Section: The Eu-poverty and Migrationmentioning
confidence: 99%
“…However, reports suggest that precarious work circumstances and gendered labour market conditions mean that many migrant families suffer from poverty and social exclusion derived from poverty, especially in the initial years after their arrival [4,34]. Evidence also suggests that ethnicity and poverty combine at local level with underlying issues of racism and class [36], to place certain ethnic minority groups at clear disadvantage in terms of opportunities for employment and civic participation, with impact on children's opportunities for integration [18,22,37]. To better understand such local combinations pertaining to newly arrived children, the paper investigates policy and practice interventions aimed at tackling childhood disadvantage.…”
Section: The Case Of Scotlandmentioning
confidence: 99%